The influence of ultrasonic vibration frequency on the properties of TiN coated biomedical Ti-13Zr-13Nb - Arman Shah, Abdullah; Mas Ayu, Hassan; Rosdi, Daud; Sudin, Izman; Siti Nurul Fasehah, Ismail; Che Ghani, Che Kob; Mohammed Rafiq, Abdul Kadir (MDPI AG, 2018)
Bare biomedical grade titanium alloys are prone to degradation when in a body fluid environment. Surface coatings such as Physical Vapor Deposition (PVD) can serve as one of the options to minimize this issue. Past reports showed that the PVD coated layer consists of pores, pinholes, and columnar growths which act as channels through which the aggressive medium attacks the substrate. Duplex and multilayer coatings seem able to address this issue to varying extents but at the expense of manufacturing time and cost. In this paper, the effect of an ultrasonic vibration frequency on PVD TiN coated Ti-13Zr-13Nb biomedical alloy was studied. Disk type samples were prepared and coated with TiN at fixed conditions: bias voltage (− 125 V), substrate temperature (300 C), and nitrogen gas flow rate (300 standard cubic centimeters per minute (SCCM)). An ultrasonic vibration was then subsequently applied to the TiN coated samples at frequencies of 8 kHz and 16 kHz for 5 min. All TiN coated samples treated with ultrasonic vibrations exhibited a higher corrosion resistance than the untreated ones. Microstructure analysis under Field Emission Scanning Electron Microscopy (FESEM) conﬁrmed that the coated sample at frequencies of 16 kHz produced the most compact coating.It is believed that the hammering effect of the ultrasonic vibration reduced the micro channels’ size in the coating and thus decelerated the corrosion’s attack.